Peroxiredoxin 2 regulates DAF-16/FOXO mediated mitochondrial remodelling in response to exercise that is disrupted in ageing - Qin Xia; Penglin Li; José C. Casas-Martinez; Antonio Miranda-Vizuete; Emma McDermott; Peter Dockery; Katarzyna Goljanek-Whysall; Brian McDonagh (Elsevier, 2024)
Objectives: A decline in mitochondrial function and increased susceptibility to oxidative stress is a hallmark of ageing. Exercise endogenously generates reactive oxygen species (ROS) in skeletal muscle and promotes mitochondrial remodelling resulting in improved mitochondrial function. It is unclear how exercise induced redox signalling results in alterations in mitochondrial dynamics and morphology. Methods: In this study, a Caenorhabditis elegans model of exercise and ageing was used to determine the mechanistic role of Peroxiredoxin 2 (PRDX-2) in regulating mitochondrial morphology. Mitochondrial morphology was analysed using transgenic reporter strains and transmission electron microscopy, complimented with the analysis of the effects of ageing and exercise on physiological activity. Results: The redox state of PRDX-2 was altered with exercise and ageing, hyperoxidised peroxiredoxins were detected in old worms along with basally elevated intracellular ROS. Exercise generated intracellular ROS and rapid mitochondrial remodelling, which was disrupted with age. The exercise intervention promoted mitochondrial ER contact sites (MERCS) assembly and increased DAF-16/FOXO nuclear localisation. The prdx-2 mutant strain had a disrupted mitochondrial network as evidenced by increased mitochondrial fragmentation. In the prdx-2 mutant strain, exercise did not activate DAF-16/FOXO, mitophagy or increase MERCS assembly. The results demonstrate that exercise generated ROS increased DAF-16/FOXO transcription factor nuclear localisation required for activation of mitochondrial fusion events that were blunted with age. Conclusions: The data demonstrate the critical role of PRDX-2 in orchestrating mitochondrial remodelling in response to a physiological stress by regulating redox dependent DAF-16/FOXO nuclear localisation.